Sprint Interval Exercise Performance in Vegans. Issue 4 (19th May 2022) - Pfeiffer, Astrid; Tomazini, Fabiano; Bertuzzi, Romulo; Lima-Silva, Adriano Eduardo
Abstract: Objective: The impact of a vegan diet on sprint interval exercise performance is unknown. Thus, the purpose of the present study was to compare performance during a sprint interval exercise between omnivores and vegans. Methods: Nine healthy omnivores (4 men and 5 women) and nine healthy vegans (4 men and 5 women), with similar levels of daily physical activity, performed four bouts (5-min rest between bouts) of a 30-s all-out sprint exercise on a cycle ergometer. Peak power, mean power, fatigue index, and time to reach maximal power output in each bout were recorded. Results: There was a higher peak power in bouts 1 and 2 compared with bouts 3 and 4 ( p < 0.02), and a higher mean power in bout 1 compared with bouts 2, 3 and 4 ( p < 0.02). However, for all bouts, there were no significant difference between omnivores and vegans in peak power (7.60 ± 1.55 vs . 8.16 ± 1.27, 7.52 ± 1.6 vs 7.61 ± 0.73, 7.00 ± 1.44 vs . 7.00 ± 1.05 and 6.95 ± 1.42 vs . 6.49 ± 0.90 W.kg −1, all p > 0.05) and in mean power (5.35 ± 0.93 vs . 5.69 ± 0.84, 5.10 ± 0.88 vs . 5.21 ± 0.49, 4.79 ± 0.81 vs . 4.79 ± 0.45 and 4.81 ± 0.81 vs . 4.69 ± 0.47 W.kg −1, all p > 0.05). Fatigue index and time to reach maximal power output were not affected by diet or bouts (all p > 0.05). Conclusions: These findings indicate that a vegan diet does not compromise sprint interval exercise performance.